PENGARUH MODEL QUANTUM LEARNING TERHADAP MENELAAH TEKS ULASAN SISWA KELAS VIII MTsN KOTA SOLOK SEMESTER II TAHUN PELAJARAN 2022/2023 - Nofrianti, Mita Joli; Marta, Redo Andi; Putri, Mega (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2023)
This research aims to describe the influence of the Quantum Learning model on reviewing review texts for class VIII MTsN Solok City students for the 2022/2023 academic year. This research was conducted at MTsN Solok City in class VIII semester II in February 2023. This type of research is quantitative using experimental methods. Research data was obtained through performance tests. The sample in the study consisted of 58 students who were divided into 2 classes, namely the experimental class and the control class. The experimental class uses the Quantum Learning model, the control class does not use the Quantum Learning model. The results of this research with an average score for reviewing review texts in the control class of 72.6 are more than adequate. The average score in the experimental class is 84.7 with good qualifications. To determine whether or not there is an influence of the Quantum Learning model, a prerequisite test for data normality using the Lilliefors test is carried out, and a homogeneity test using the F test. Followed by hypothesis testing using the t test with the condition that sig < 0.05. The results of this test show that there is an influence of the Quantum Learning model on reviewing students' review texts because in the t test table the value obtained is tcount = 14.83 > ttable = 2.763. So H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of the Quantum Learning model on reviewing review texts for class VIII students in the second semester of MTsN Solok City for the 2022/2023 academic year.